CHARACTERS AND MORAL VALUES IN THE NOVEL OF LETHAL WHITE BY J.K ROWLING (A CORMORAN STRIKE NOVEL ROBERTH GALBRAITH) - Benning Rizahra; Supeno Supeno (Universitas Indraprasta PGRI, 2019)
Abstract: The purpose of this thesis to analyze the character and moral value in Lethal White novel by J.K Rowling. The method used in this research is descriptive qualitative research that aims to describe the character and moral value contained in Lethal White novel by J.K Rowling. The data obtained are then analyzed and clarified based on the protagonist, antagonist, secondary, extras, round and flat character. Likewise with the moral value that is divided into honestly, altruism, diligence, and solidarity. After analyzing the characters and moral values in Lethal White novel by J.K Rowling, the writer found two points from the discussion characters and moral values, 1) there are protagonist is 47%, antagonist 33%, secondary 11%, extras 6%, flat 1%, round 1%. The protagonist character gets the highest percentage. 2) there are 11% honesty, 33% altruism, 33% diligence, and 22% solidarity. Diligence and altruism actually get the same percentage since the author would like to tell the reader that to gains dream, people need to be diligence and in this life, sometimes it is god for being altruism.Key Words: character; moral value; and novel.